Application of biologically active additives from sea buckthorn fruits in macaroni production technology - Z. A. Ivanova; F. K. Tkhazeplova (Новые технологии)
The article presents the results of the research on the development of pasta recipes using sea buckthorn bioadditives in the form of powder and in the form of protein-lipid puree. An increase in the content of P-carotene, bioflavonoids, tocopherols, ascorbic acid, phylloquinone, phytosterol, pectin and potassium, when the bioadditive in the form of sea-buckthorn fruit powder is included in the recipe for making pasta has been established.